Ben Yokoyama and the Cookies of Chaos - Book 5 - Swanson, Matthew, 1974-; Behr, Robbi (New York : Alfred A. Knopf, 2023)
While attempting to return a lost wallet to its owner, Ben tries out different life philosophies inspired by his friends, family, and fortune cookies.
Ages 8-12.
Keywords: Proverbs -- Juvenile fiction; Conduct of life -- Juvenile fiction; Lost and found possessions -- Juvenile fiction; Fortune cookies -- Juvenile fiction; Proverbs -- Fiction; Conduct of life -- Fiction; Lost and found possessions -- Fiction; Fortune cookies -- Fiction; Novels